Dehydroepiandrosterone sulfate levels and risk of atrial fibrillation: The Rotterdam Study. (29th August 2020) - Krijthe, Bouwe P; de Jong, Frank H; Hofman, Albert; Franco, Oscar H; Witteman, Jacqueline CM; Stricker, Bruno HC; Heeringa, Jan
Abstract: Background: High plasma dehydroepiandrosterone sulfate (DHEAS) levels have been associated with a reduced risk of cardiovascular disease and atherosclerosis. To our knowledge, no previous follow-up study has investigated the association between DHEAS and the development of atrial fibrillation. Our objective was to investigate the association between DHEAS levels and incident atrial fibrillation. Methods and results: The study was based on a random sample within the prospective population-based Rotterdam Study. The study population comprised 1180 participants without atrial fibrillation at baseline for whom baseline levels of DHEAS were measured in plasma. Atrial fibrillation was ascertained from centre visit electrocardiogram (ECG) assessments as well as medical records. During a mean follow-up period of 12.3 years, 129 participants developed atrial fibrillation. DHEAS levels were inversely associated with the risk of atrial fibrillation (hazard ratio (HR) per standard deviation (SD): 0.74, 95% confidence interval (CI): 0.58–0.94). Subjects in the highest DHEAS quartile had an almost three times lower risk of atrial fibrillation during follow-up, compared to those in the lowest DHEAS quartile (HR: 0.34, 95% CI: 0.18–0.64) adjusted for age, sex and cardiovascular risk factors. Conclusion: DHEAS can be regarded as an important indicator of future atrial fibrillation in both men and women, independent of known cardiovascular risk factors.